Living as a family in the midst of chronic illness. Issue 1 (15th January 2013) - Årestedt, Liselott; Persson, Carina; Benzein, Eva
<x xml:space="preserve">Abstract</x> Aims and objectives The aim of the study was to illuminate the meaning of lived experience of living as a family in the midst of chronic illness. Background Chronic illness implies a change for both the individual and the family. In this changed situation, all family members seem to benefit from sharing experiences and receiving support. Current research highlights the individual patient's or family member's perspectives on chronic illness, but family systems nursing (FSN) studies are warranted. Design A qualitative design with a FSN approach was chosen. Method Repeated qualitative narrative interviews with seven families living with chronic illness were performed. A phenomenological hermeneutic analysis, inspired by Ricoeur, was used to interpret the data. Results The phenomenon can be described as an ongoing movement towards well‐being. The results included two themes and five sub‐themes. The first theme was 'Co‐creating a context for living with illness' with the subthemes; 'learning to live with the expressions of illness' and 'communicating the illness within and outside the family'. The second theme was 'Co‐creating alternative ways for everyday life' with the subthemes; 'adapting to a new life rhythm', 'altering relationships' and 'changing roles and tasks in the family'. Conclusions Living as a family in the midst of chronic illness can be described as an ongoing process where the family members co‐create a context for living with illness. They also co‐create a context for alternative ways of everyday life. Relevance to clinical practice Knowledge about lived experience of living as a family in the midst of chronic illness can help nurses to adopt a FSN care perspective. This can increase the chances of taking advantage of the ways family members manage situations together, as well as highlight resources within the family.